The Role of Digitalization in Increasing Economic and Financial Inclusion in South Papuan Communities - Putu Nita Yulianti, Ni Luh; Adi Maulana Rachman; Apolinaris S Awotkay; Gusti Putu Eka Kusuma; Soleha, Soleha (CV. Ulil Albab Corp, 2026)
This study analyzes the role of digitalization in enhancing economic and financial inclusion in South Papua by examining digital infrastructure conditions, the utilization of technology-based financial services, impacts on local businesses, socio-cultural influences, and links to regional socioeconomic indicators. A descriptive qualitative approach was employed, using in-depth interviews with policymakers, financial service providers, community leaders, business actors, and both users and non-users of digital services. Secondary data from the 2025 South Papua Statistics Agency (BPS) supported the analysis. Findings reveal uneven telecommunications infrastructure, with only 6.96% of villages having very strong signals and 13.77% lacking signal access. Adoption of digital financial services, including mobile banking and e-wallets, remains limited in rural areas due to poor connectivity, low device ownership, and inadequate digital literacy. However, businesses adopting digital platforms reported revenue increases of 20–30% through market expansion. Socio-cultural factors influence technology acceptance, with younger generations adapting more readily. The study concludes that improved connectivity positively correlates with financial inclusion and human development, recommending infrastructure expansion, internet subsidies, community-based digital literacy programs, and multi-stakeholder collaboration.